Impact of universal health insurance coverage in Thailand on sales and market share of medicines for non-communicable diseases: an interrupted time series study. Issue 6 (28th November 2012) - Garabedian, Laura Faden; Ross-Degnan, Dennis; Ratanawijitrasin, Sauwakon; Stephens, Peter; Wagner, Anita Katharina
Abstract : Objective: In 2001, Thailand implemented the Universal Coverage Scheme (UCS), a public insurance system that aimed to achieve universal access to healthcare, including essential medicines, and to influence primary care centres and hospitals to use resources efficiently, via capitated payment for outpatient services and other payment policies for inpatient care. Our objective was to evaluate the impact of the UCS on utilisation of medicines in Thailand for three non-communicable diseases: cancer, cardiovascular disease and diabetes. Design: Interrupted time-series design, with a non-equivalent comparison group. Setting: Thailand, 1998–2006. Data: Quarterly purchases of medicines from hospital and retail pharmacies collected by IMS Health between 1998 and 2006. Intervention: UCS implementation, April–October 2001. Outcome measures: Total pharmaceutical sales volume and percent market share by licensing status and National Essential Medicine List status. Results: The UCS was associated with long-term increases in sales of medicines for conditions that are typically treated in outpatient primary care settings, such as diabetes, high cholesterol and high blood pressure, but not for medicines for diseases that are typically treated in secondary or tertiary care settings, such as heart failure, arrhythmias and cancer. Although the majority of increases in sales were for essential medicines, there were also postpolicy increases in sales of non-essential medicines. Immediately following the reform, there was a significant shift in hospital sector market share by licensing status for most classes of medicines. Government-produced products often replaced branded generic or generic competitors. Conclusions: Our results suggest that expanding health insurance coverage with a medicine benefit to the entire Thai population increased access to medicines in primary care. However, our study also suggests that the UCS may have had potentially undesirable effects. Evaluations of the long-term impacts of universal health coverage on medicine utilisation are urgently needed.